Building health across generations: Unraveling the impact of early childcare on maternal health - Mara Barschkett; Laia Bosque-Mercader (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
In contemporary households, women often shoulder most organisation and caregiving responsibilities leading them to play a crucial role in family dynamics. While previous research has established that public early childcare affects child outcomes and maternal employment, less attention has been given to its effects on maternal health despite its relevance within the household. This study investigates the impact of public early childcare on maternal short- and long-term health. Based on administrative health records covering 90% of the German population over a decade, we leverage the exogenous variation in childcare coverage rates across counties and time induced by a major German early childcare expansion. Our results reveal an intra-household transmission of communicable diseases: mothers experience 4-8% more infections and 2-4% more respiratory diseases for a 10 percentage point rise in childcare coverage rates when their children are 1-2 years old. In contrast, mothers benefit from reductions in obesity and anaemia, and heterogeneity analyses show a lower prevalence of mood- and stress-related disorders for multiparous and older mothers. The policy implications of our findings extend beyond the health impacts of early childcare on mothers and shed light on the broader dynamics within families.
Keywords: I10; I12; J13; D64; 330; childcare; maternal health; administrative health data; intergenerational effects